Logics of Organization Theory : Audiences, Codes, and Ecologies - Hannan, Michael T. (Book collections on Project MUSE., 2011)
Building theories of organizations is challenging: theories are partial and "folk" categories are fuzzy. The commonly used tools--first-order logic and its foundational set theory--are ill-suited for handling these complications. Here, three leading authorities rethink organization theory. Logics of Organization Theory sets forth and applies a new language for theory building based on a nonmonotonic logic and fuzzy set theory. In doing so, not only does it mark a major advance in organizational theory, but it also draws lessons for theory building elsewhere in the social sciences. Organizat.